THE IMPLEMENTATION OF SOFTSKILL ESSENCES ON VOCATIONAL EDUCATION - Sukardi; Ahmad Eko Suryanto; Ratna Pancawati (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
At present days stakeholders require the graduates who have the technical skills (Hardskill) as well possess the soft skills. The Hardskills are just not sufficient to deal with the qualification of employers in the real-world of workplace, but need to be equipped with soft skills in order to shape the integrated capabilities as needed by users. To form the student’s soft skills can be implemented through the coaching program in formal learning activities and extracurricular activities. The softskill development of students is necessary to be achieved with concrete efforts, namely: 1) the existence of policies that legalize the implementation of soft skill based on the extracurricular activities in each education unit; 2) systematic and planned soft skills development program; and 3) the softskill dissemination is carried out synergistically involving all parties.